Fractalkine/CX3CL1 engages different neuroprotective responses upon selective glutamate receptor overactivation - Lauro, Clotilde; Catalano, Myriam; Di Paolo, Eleonora; Chece, Giuseppina; de Costanzo, Ida; Trettel, Flavia; Limatola, Cristina (Frontiers in Cellular Neuroscience, 2015)
Neuronal death induced by overactivation of N-methyl-d-aspartate receptors (NMDARs) is implicated in the pathophysiology of many neurodegenerative diseases such as stroke, epilepsy and traumatic brain injury. This toxic effect is mainly mediated by NR2B-containing extrasynaptic NMDARs, while NR2A-containing synaptic NMDARs contribute to cell survival, suggesting the possibility of therapeutic approaches targeting specific receptor subunits. We report that fractalkine/CX3CL1 protects hippocampal neurons from NMDA-induced cell death with a mechanism requiring the adenosine receptors type 2A (A2AR). This is different from CX3CL1-induced protection from glutamate-induced cell death, that fully depends on A1R and requires in part A3R. We show that CX3CL1 neuroprotection against NMDA excitotoxicity involves D-serine, a co-agonist of NR2A/NMDAR, resulting in cyclic AMP-dependent transcription factor (CREB) phosphorylation.